Strafrecht in Ungarn (1920 – 1944) - Veronika Lehotay (Journal on European History of Law, 2023)
The study deals with criminal law between the two world wars. The first codified Hungarian Penal Code was completed in 1878. The Criminal Code became known as the Csemegi Code. After 1920, there were also a number of changes in criminal law. The main questions of this paper are: How did the economic crisis, the war, and the increasing discrimination from 1938 onward affect criminal law? In the context of the period between 1920 and 1944, the question arises how and whether the representatives of (criminal) jurisprudence took a stand on equality, war and restriction of rights. How has the relationship between the state and the individual changed with regard to public law / criminal law? How did the criminal law tendency appear in Hungarian jurisprudence and how did it influence legislation? How did racial protection appear in Hungarian criminal law thought and practice? How did criminal law develop in practice in Hungary between 1920 and 1944? How did the law of criminal procedure change? The main sources for the research are the legislation and the literature of the time.